Comparison Between Qualitative and Quantitative Research Approaches: Social Sciences - Mehrad, Aida; Zangeneh, Mohammad Hossein Tahriri (International Journal For Research In Educational Studies, 2019)
Nowadays because of the vast of investigations and high level of technology, majority of investigators endeavor to apply appropriate methods in their research; in this case, focusing on research approaches assumed as one of the critical factors in the science world. In research methodology specifically in the social science area, two approaches of qualitative and quantitative have been considered more. These approaches assumed as two practical and essential methods in most investigations. Therefore, the purpose of the current literature review is to distinguish the imperative comparison of quantitative and qualitative in the research methodology and determining the brilliant differences between these two research factors. Furthermore, realizing the accurate approach and apply it in the correct way in every investigation is super important; then, the researchers endeavor to justify this essential fact for future studies.